Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 176 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Aetheorhiza bulbosa (L.) Cass.", "HasGeospatialIssue is false", "Geometry POLYGON((-5.01 42.61,-5.01 45.75,1.88 45.75,1.88 42.61,-5.01 42.61))" ] } The dataset includes 176 records from 10 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0085470-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences